Carbon nanotubes as VEGF carriers to improve the early vascularization of porcine small intestinal submucosa in abdominal wall defect repair - Liu Z (Dove Medical Press, 2014)
Zhengni Liu,1,* Xueyi Feng,2,* Huichun Wang,1 Jun Ma,1 Wei Liu,3 Daxiang Cui,4 Yan Gu,1 Rui Tang,11Department of General Surgery, Shanghai Ninth People’s Hospital, Hernia and Abdominal Wall Disease Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of General Surgery, Lu’an People’s Hospital, Lu’an Affiliated Hospital of Anhui Medical University, Lu’an, Province Anhui, People’s Republic of China; 3Department of Plastic and Reconstructive Surgery, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai Key Laboratory of Tissue Engineering, Shanghai, People’s Republic of China; 4Institute of Nano Biomedicine and Engineering, Key Laboratory for Thin Film and Microfabrication Technology of the Ministry of Education, Research Institute of Micro/Nano Science and Technology, Bio-X Center, Shanghai Jiao Tong University, Shanghai, People's Republic of China *These authors contributed equally to this work Abstract: Insufficient early vascularization in biological meshes, resulting in limited host tissue incorporation, is thought to be the primary cause for the failure of abdominal wall defect repair after implantation. The sustained release of exogenous angiogenic factors from a biocompatible nanomaterial might be a way to overcome this limitation. In the study reported here, multiwalled carbon nanotubes (MWNT) were functionalized by plasma polymerization to deliver vascular endothelial growth factor165 (VEGF165). The novel VEGF165-controlled released system was incorporated into porcine small intestinal submucosa (PSIS) to construct a composite scaffold. Scaffolds incorporating varying amounts of VEGF165-loaded functionalized MWNT were characterized in vitro. At 5 weight percent MWNT, the scaffolds exhibited optimal properties and were implanted in rats to repair abdominal wall defects. PSIS scaffolds incorporating VEGF165-loaded MWNT (VEGF–MWNT–PSIS) contributed to early vascularization from 2–12 weeks postimplantation and obtained more effective collagen deposition and exhibited improved tensile strength at 24 weeks postimplantation compared to PSIS or PSIS scaffolds, incorporating MWNT without VEGF165 loading (MWNT–PSIS). Keywords: vascular endothelial growth factor165, controlled release, multi-walled carbon nanotube, early vascularization